Molten salt strategy and plasma technology induced MnO2 with oxygen vacancy for high performance Zn-ion batteries. (17th November 2021) - Shao, Fuqiang; Li, Shuke; Xu, Yanchao; Jiao, Yang; Chen, Jianrong
Abstract : The oxygen vacancy-rich MnO2  was synthesized by the molten salt method and the plasma etching strategy. The amorphous layer increased the active sites and the oxygen vacancies on the surface of MnO2  that promoted the rapid transfer of charges. Abstract : The low cost, high energy density, high theoretical capacity and environmental friendliness of manganese dioxide (MnO2 ) make it a promising electrode material for aqueous zinc-ion batteries. However, poor conductivity and insufficient active sites of MnO2 hinder its further development. In this study, a molten salt method and plasma technology are proposed to synthesize an amorphous layer and oxygen vacancies on the surface of MnO2, promoting enhanced charge transport and increased exposed active sites. Originating from its unique electronic structure, the as-prepared MnO2 -3 possesses a high discharge capacity of 252 mA h g −1 at a current density of 0.1 A g −1, and the capacity retention rate is 81% after 100 cycles. In addition, the sample shows lower polarization and charge transfer resistance. The results of this study show that the molten salt method combined with the plasma treatment technology has a promising prospect in the field of electrochemical energy storage.